2019
DOI: 10.1038/s41598-019-40222-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically guided non-invasive CRISPR-Cas9/gRNA delivery across blood-brain barrier to eradicate latent HIV-1 infection

Abstract: CRISPR-Cas9/gRNA exhibits therapeutic efficacy against latent human immunodeficiency virus (HIV) genome but the delivery of this therapeutic cargo to the brain remains as a challenge. In this research, for the first time, we demonstrated magnetically guided non-invasive delivery of a nano-formulation (NF), composed of Cas9/gRNA bound with magneto-electric nanoparticles (MENPs), across the blood-brain barrier (BBB) to inhibit latent HIV-1 infection in microglial (hμglia)/HIV (HC69) cells. An optimized ac-magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 41 publications
(41 reference statements)
2
84
0
Order By: Relevance
“…However, several challenges have to be overcome such as in vivo delivery in the brain and long-term toxicity before its use in the clinic and thus needs far more investigations. An original way to deliver CRISPR/cas9 guided RNA across the BBB has been developed recently and hold promises (Kaushik et al, 2019). Notably, it was shown that this non-invasive method which uses magnetically guided delivery of RNAs inhibits latent infection of microglial cells and cross the BBB in in vitro models.…”
Section: Resultsmentioning
confidence: 99%
“…However, several challenges have to be overcome such as in vivo delivery in the brain and long-term toxicity before its use in the clinic and thus needs far more investigations. An original way to deliver CRISPR/cas9 guided RNA across the BBB has been developed recently and hold promises (Kaushik et al, 2019). Notably, it was shown that this non-invasive method which uses magnetically guided delivery of RNAs inhibits latent infection of microglial cells and cross the BBB in in vitro models.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Kaushik et al developed a magnetic nanoformulation consisting of genome editing Cas9/gRNA bound with magneto-electric nanoparticles with the aim of targeting HIV-1 long terminal repeat, thereby stopping viral transcription and eradicating latent HIV infection. This is a very innovative approach deserving further investigation and that could potentially have clinical utility in the management of HIV infection of the brain [158].…”
Section: Approaches To Eliminating the Hiv-1 Brain Reservoirmentioning
confidence: 99%
“…However, this technique still requires an effective method for delivery across the BBB. To overcome this obstacle, it has been combined with magnetic nanodelivery systems, showing a significant HIV-LTR reduction, indicating a potential therapy to eliminate latent HIV infection in the brains of opioid abusers (Figure 1C) (208).…”
Section: New Technologies and Potential Therapiesmentioning
confidence: 99%